ChemInform Abstract: Microwave Irradiation and Phase Transfer Catalysis in C‐, O‐ and N‐Alkylation Reactions. Issue 9 (March 2015) - Keglevich, Gyorgy; Grun, Alajos; Balint, Erika
Abstract Review: 78 refs.